The Effect of Using Webtoon Apps on Students’ Vocabulary Mastery - Lala Dini Arsika; Ashari P Swondo (Edumaspul: Jurnal Pendidikan, 2025)
This research examines how the Webtoon application influences students’ vocabulary mastery. A quasi-experimental design was applied to two tenth-grade classes (MP 1 and RPL 2) at SMK Swasta PAB 2 Helvetia, involving a total of 40 students who were separated into an experimental class and a control class. The experimental group learned vocabulary through the Webtoon application, while the control group received instruction using conventional printed materials. Vocabulary assessments were administered as pre-test and post-test to determine students’ progress. The results demonstrated that the experimental group achieved a noticeably higher improvement, with an average post-test score of 76.60 compared to 59.20 in the control group. The paired sample test obtained a significance value of 0.000 (p < 0.05), indicating that the use of Webtoon had a meaningful and significant impact on students’ vocabulary development. Therefore, Webtoon, as a digital comic-based learning medium, is considered effective in providing contextual vocabulary exposure and enhancing student engagement, making it a suitable digital tool to support English vocabulary learning.